Toughened polyamide
Patent Information
- Application Number
- CN202580023226.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-26
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这些增韧聚酰胺具有较差的热老化特性,导致在持续暴露于高温(例如,大于150℃)后机械性能显著劣化
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Cross Reference to Related Applications
[0001] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 639,263, filed April 26, 2024, the contents of which are incorporated herein in their entirety. TECHNICAL FIELD
[0002] The present disclosure relates to polymeric compositions, and more specifically, to polymeric compositions comprising polyamides. BACKGROUND
[0003] Maleic anhydride grafted polyethylene has long been used to toughen polyamides. However, these toughened polyamides have poor heat aging characteristics, resulting in significant degradation of mechanical properties upon continued exposure to high temperatures (e.g., greater than 150 °C). As a result, these toughened polyamides are not suitable for high temperature applications, such as internal combustion engine intake manifolds. SUMMARY
[0004] Accordingly, it would be desirable to have a toughened polyamide that retains its mechanical properties upon heat aging. Embodiments of the present disclosure meet this need by mixing a polyamide with an epoxy-functional polyolefin and a functionalized polyolefin comprising a polyolefin bearing an ethylenically unsubstituted dicarboxylic acid or derivative thereof, wherein the molar ratio of epoxy-functional groups to the ethylenically unsubstituted dicarboxylic acid or derivative thereof is from 20 to 235. Generally, the poor heat aging performance of toughened polyamides is caused by the presence of unreacted acid functional groups (e.g., anhydride) that catalyze degradation of the polyamide backbone. It is believed that using a specific molar ratio of epoxy-functional groups to the ethylenically unsubstituted dicarboxylic acid or derivative thereof (e.g., from 20 to 235) prevents degradation of the polyamide backbone while still sufficiently toughening the composition.
[0005] Embodiments of the present disclosure relate to a composition comprising: a polyamide; an epoxy-functional polyolefin, the epoxy-functional polyolefin comprising one or more epoxy ring functional groups; and a functionalized polyolefin, the functionalized polyolefin comprising a polyolefin bearing an ethylenically unsubstituted dicarboxylic acid or derivative thereof, and wherein the molar ratio of epoxy-functional groups to the ethylenically unsubstituted dicarboxylic acid or derivative thereof is from 20 to 235.
[0006] These and other embodiments are described in greater detail in the detailed description. It should be understood that both the foregoing general description and the following detailed description present embodiments of the disclosed technology and are intended to provide an overview or framework for understanding the nature and character of the technology as claimed. The accompanying drawings are included to provide a better understanding of the technology, and are incorporated in and constitute a part of this specification. DETAILED DESCRIPTION
[0007] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Therefore, the general term polymer encompasses the term "homopolymer," which is typically used to refer to a polymer prepared from only one type of monomer; and "copolymer," which refers to a polymer prepared from two or more different types of monomers.
[0008] "Polyethylene" or "ethylene-based polymer" refers to a polymer containing more than 50% by weight of monomers derived from ethylene. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more monomer types). Common forms of polyethylene known in the art include low-density polyethylene (LDPE); linear low-density polyethylene (LLDPE); ultra-low-density polyethylene (ULDPE); very low-density polyethylene (VLDPE); single-point catalytic linear low-density polyethylene, including both linear and substantially linear low-density resins (m-LLDPE); medium-density polyethylene (MDPE); and high-density polyethylene (HDPE).
[0009] The term "LDPE" can also be referred to as "high-pressure ethylene polymer" or "highly branched polyethylene," and is defined as meaning that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator (such as peroxide) (see, for example, U.S. Patent No. 4,599,392, which is incorporated herein by reference in its entirety). LDPE resin typically has a viscosity of 0.916 g / cm³. 3 Up to 0.930 g / cm 3 The density within the range.
[0010] The term "LLDPE" includes: resins produced using Ziegler-Natta catalyst systems and resins produced using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphine imides, and geometry-restricted catalysts; and resins produced using post-metallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also known as polyaryloxy ether catalysts). LLDPE includes linear, substantially linear, or heterogeneous ethylene-based copolymers. LLDPE contains fewer long-chain branchings than LDPE and comprises substantially linear ethylene polymers, further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, each of which is incorporated herein by reference in its entirety; homogeneous branched linear ethylene polymer compositions, such as those described in U.S. Patent No. 3,645,992, which is incorporated herein by reference in its entirety; heterogeneous branched ethylene polymers, such as those prepared according to the method disclosed in U.S. Patent No. 4,076,698, which is incorporated herein by reference in its entirety; and blends thereof (such as those disclosed in U.S. Patent Nos. 3,914,342 and 5,854,045), which are incorporated herein by reference in their entirety. LLDPE resins can be prepared via gas-phase, solution-phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0011] The term "HDPE" typically refers to a density greater than approximately 0.930 g / cm³. 3 And at most about 0.970 g / cm³ 3 Polyethylene, which is generally prepared using Ziegler-Natta catalysts, chromium catalysts or single-point catalysts (including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly known as metallocenes), confined geometry catalysts, phosphine imine catalysts and polyvalent aryloxy ether catalysts (commonly known as bisphenylphenoxy)).
[0012] As used herein, “polyolefin” refers to an olefin-based polymer. As used herein, “olefin,” also referred to as “alkene,” refers to a straight-chain, branched, or cyclic compound comprising carbon and hydrogen and having at least one double bond. As used herein, when a polymer or copolymer, such as a polyolefin elastomer, is referred to as containing an olefin, the olefin present in the polymer or copolymer is a polymeric form of the olefin.
[0013] The composition may comprise a polyamide; an epoxy-functionalized polyolefin comprising one or more epoxy ring functional groups; and a functionalized polyolefin comprising a polyolefin having an olefinically unsubstituted dicarboxylic acid or a derivative thereof.
[0014] Polyamides can be polymers containing repeating amide (-CONH-) groups. Polyamides can contain at least 20% by weight, at least 30% by weight, at least 40% by weight, at least 50% by weight, at least 51% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, or even at least 90% by weight of amide groups. Polyamides can have a melting point of 160°C to 320°C, such as 160°C to 180°C, 180°C to 200°C, 200°C to 220°C, 220°C to 240°C, 240°C to 260°C, 260°C to 280°C, 280°C to 300°C, 300°C to 320°C, or any combination of two or more of these ranges. In the embodiments, the polyamide may comprise one or more of polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, polyamide 612, polyamide 66 / 610, polyamide 666, polyamide 6 / 69, nylon 1010, nylon 1012, PA 6T, high-temperature nylon, or blends thereof. Suitable polyamides may comprise Zytel, which is available from DuPont. ® Resin.
[0015] In an embodiment, based on the total weight of the composition, the composition may contain 60% to 99% by weight, such as 60% to 65% by weight, 65% to 70% by weight, 70% to 75% by weight, 75% to 80% by weight, 80% to 85% by weight, 85% to 90% by weight, 90% to 95% by weight, 95% to 99% by weight, or any combination of two or more of these ranges of polyamide.
[0016] Epoxy-functionalized polyolefins can be polymers comprising one or more epoxy rings. In embodiments, epoxy-functionalized polyolefins can be copolymers formed from two or more monomers, at least one or more of which comprise at least one epoxy ring. Epoxy-functionalized polyolefins can contain α-olefins, such as C2-C... 20 α-Alkenes. For example, α-alkenes can be C2, C3, C4, C5, C6, C7, C8, C9 ... 10 C 11 C 12 C 13 C 14 C 15 C 16 C 17 C 18 C19 or C 20 Olefins. Epoxy-functionalized polyolefins may contain alkyl acrylates, such as methyl acrylate, ethyl acrylate, or butyl acrylate. Epoxy-functionalized polyolefins may contain monomers having epoxy functional groups, such as glycidyl groups, such as glycidyl acrylate, alkyl glycidyl acrylate, glycidyl methacrylate (GMA), or allyl glycidyl ether (AGE). Other suitable monomers having epoxy functional groups include, but are not limited to, (3,4-epoxycyclohexyl) methyl acrylate, (3,4-epoxycyclohexyl) methyl acrylate, and 1,2-epoxy-4-vinylcyclohexane. In embodiments, the epoxy-functionalized polyolefin may be containing C2-C... 20 A terpolymer of α-olefin, alkyl acrylate, and monomers having epoxy functional groups. In embodiments, the epoxy-functionalized polyolefin may be a terpolymer comprising ethylene, butyl acrylate, and glycidyl methacrylate (E / nBA / GMA). In embodiments, the epoxy-functionalized polyolefin (such as a terpolymer of ethylene, alkyl acrylate, and alkyl glycidyl acrylate) may contain 1% to 15% by weight, such as 1% to 3% by weight, 3% to 5% by weight, 5% to 8% by weight, 8% to 12% by weight, 12% to 15% by weight, or any combination of two or more of these ranges of alkyl glycidyl acrylate; and 10% to 40% by weight, such as 10% to 15% by weight, 15% to 20% by weight, 20% to 25% by weight, 25% to 30% by weight, 30% to 35% by weight, 35% to 40% by weight, or any combination of two or more of these ranges of alkyl acrylate. Epoxy-functionalized polyolefins may have a melt index (I2) of 1.0 g / 10 min to 30 g / 10 min, such as 1.0 g / 10 min to 3.0 g / 10 min, 3.0 g / 10 min to 6.0 g / 10 min, 6.0 g / 10 min to 10 g / 10 min, 10 g / 10 min to 15 g / 10 min, 10 g / 10 min to 15 g / 10 min, 15 g / 10 min to 20 g / 10 min, 20 g / 10 min to 25 g / 10 min, 25 g / 10 min to 30 g / 10 min, or any combination of two or more of these ranges. As those skilled in the art will understand, the concentration of epoxy functional groups can be measured by nuclear magnetic resonance (NMR).
[0017] In embodiments, based on the total weight of the composition, the composition may contain 0.8 wt% to 39 wt% of epoxy-functionalized polyolefins, such as 0.8 wt% to 2 wt%, 2 wt% to 4 wt%, 4 wt% to 8 wt%, 8 wt% to 12 wt%, 12 wt% to 15 wt%, 15 wt% to 20 wt%, 20 wt% to 25 wt%, 25 wt% to 30 wt%, 30 wt% to 35 wt%, 35 wt% to 39 wt%, or any combination of two or more of these ranges.
[0018] As previously mentioned, the composition may contain a functionalized polyolefin. The functionalized polyolefin may contain at least one α-olefin, such as C2-C... 14 α-olefins. Expected C2-C 14 α-olefins include, for example, but not limited to, C2, C3, C4, C5, C6, C7, C8, C9 ... 10 C 11 C 12 C 13 Or C 14 α-Olefins. In embodiments, the α-olefin may be ethylene, and the functionalized polyolefin may comprise functionalized polyethylene. In embodiments, the polyolefin may comprise LLDPE, HDPE, polyolefin elastomers (such as polyethylene elastomers), or polyolefin plasmons. In embodiments, the functionalized polyolefin may comprise at least two α-olefins. For example, the functionalized polyolefin may comprise ethylene and C3-C... 14 α-olefins.
[0019] Functionalized polyolefins can be functionalized with olefinically unsubstituted dicarboxylic acids or their derivatives. Functionalized polyolefins can be formed by copolymerizing olefinically unsubstituted dicarboxylic acids or their derivatives with one or more α-olefins or by grafting olefinically unsubstituted dicarboxylic acids or their derivatives onto a polyolefin. olefinically unsubstituted dicarboxylic acids or their derivatives can be selected from maleic anhydride, itaconic anhydride, maleic acid diester, fumarate diester, maleic acid monoester or fumarate monoester, esters of C1 to C4 alcohols, maleic acid, itaconic acid, fumarate, or mixtures thereof. For example, functionalized polyolefins (such as functionalized polyethylene) can include anhydride-functionalized polyolefins, such as maleic anhydride-functionalized polyolefins, such as maleic anhydride-functionalized polyethylene, such as maleic anhydride-grafted polyolefins. The functionalized polyolefin may have a functionalization level of 0.1 wt% to 3.0 wt%, such as 0.15 wt% to 2.0 wt%, 0.1 wt% to 0.5 wt%, 0.5 wt% to 1.0 wt%, 1.0 wt% to 1.5 wt%, 1.5 wt% to 2.0 wt%, 2.0 wt% to 2.5 wt%, 2.5 wt% to 3.0 wt%, or any combination of two or more of these ranges, of an olefinically bonded unsubstituted dicarboxylic acid or a derivative thereof. In embodiments, the functionalized polyolefin may have been grafted with maleic anhydride at a level of 0.1 wt% to 3.0 wt%, such as 0.15 wt% to 2.0 wt%, 0.1 wt% to 0.5 wt%, 0.5 wt% to 1.0 wt%, 1.0 wt% to 1.5 wt%, 1.5 wt% to 2.0 wt%, 2.0 wt% to 2.5 wt%, 2.5 wt% to 3.0 wt%, or any combination of two or more of these ranges. As those skilled in the art will understand, the concentration of olefinically unsubstituted dicarboxylic acids (or their derivatives) can be measured by Fourier transform infrared (FTIR).
[0020] Functionalized polyolefins (such as polyethylene elastomers) may have densities ranging from 0.855 g / cc to 0.890 g / cc, such as 0.855 g / cc to 0.860 g / cc, 0.860 g / cc to 0.865 g / cc, 0.865 g / cc to 0.875 g / cc, 0.875 g / cc to 0.880 g / cc, 0.880 g / cc to 0.885 g / cc, 0.885 g / cc to 0.890 g / cc, or any combination of two or more of these ranges. Functionalized polyolefins may have a melt index (I2) of 0.1 dg / min to 15 dg / min, such as 0.1 dg / min to 0.5 dg / min, 0.5 dg / min to 1.0 dg / min, 1.0 dg / min to 3.0 dg / min, 3.0 dg / min to 5 dg / min, 5 dg / min to 10 dg / min, 10 dg / min to 15 dg / min, or any combination of two or more of these ranges.
[0021] In embodiments, based on the total weight of the composition, the composition may contain 0.1 wt% to 8 wt%, such as 0.1 wt% to 0.5 wt%, 0.5 wt% to 1 wt%, 1 wt% to 2 wt%, 2 wt% to 3 wt%, 3 wt% to 4 wt%, 4 wt% to 5 wt%, 5 wt% to 6 wt%, 6 wt% to 7 wt%, 7 wt% to 8 wt%, or any combination of two or more of these ranges of functionalized polyolefin.
[0022] In embodiments, the composition may further comprise one or more epoxy oils or epoxy resins. Epoxy oils or epoxy resins may comprise, for example, epoxidized vegetable oils, such as epoxidized soybean oil. Such oils may contain ethylene oxide and may have an ethylene oxide oxygen level of up to 8%. In embodiments, the composition may comprise up to 10% by weight, such as 0 to 10% by weight, 0.1% to 10% by weight, 0 to 0.1% by weight, 0.1% to 0.5% by weight, 0.5% to 1% by weight, 1% to 2% by weight, 2% to 4% by weight, 4% to 6% by weight, 6% to 8% by weight, 8% to 10% by weight, or any combination of two or more of these ranges of epoxy oil or epoxy resin. It should be understood that the ratio of epoxy functional groups includes both epoxy functional groups in the epoxy-functionalized polyolefin and epoxy functional groups in the epoxy oil or epoxy resin.
[0023] The composition may include inorganic fillers, which can reduce cost or increase hardness. Suitable inorganic fillers may include CaCO3, clay, talc, fly ash, carbon black, silica, and glass fiber. Generally, inorganic fillers, such as CaCO3, can provide both volume filling and hardening properties at a low cost. Inorganic fillers may have particle sizes or fiber diameters ranging from 0.01 micrometers to 300 micrometers, such as 0.01 micrometers to 30 micrometers, 0.5 micrometers to 1 micrometer, 1 micrometer to 5 micrometers, 5 micrometers to 10 micrometers, 10 micrometers to 15 micrometers, 15 micrometers to 30 micrometers, 30 micrometers to 50 micrometers, 50 micrometers to 100 micrometers, 100 micrometers to 200 micrometers, 200 micrometers to 300 micrometers, or any combination of two or more of these ranges. When using fibers, the fibers may have a length less than 10 mm, such as less than 5 mm, less than 3 mm, less than 1 mm, at least 10 micrometers, at least 50 micrometers, at least 100 micrometers, at least 500 micrometers, at least 1000 micrometers, 10 to 100 micrometers, 100 to 250 micrometers, 250 to 500 micrometers, 500 to 1000 micrometers, 1000 to 2000 micrometers, 2000 to 3000 micrometers, or any combination of two or more of these ranges. In embodiments, the composition may contain 0% to 40% by weight, such as 0% to 30% by weight, 0% to 20% by weight, 0% to 10% by weight, 0% to 5% by weight, 0% to 1% by weight, 1% to 40% by weight, 1% to 30% by weight, 1% to 20% by weight, or 1% to 10% by weight of inorganic filler.
[0024] It should be understood that the above compositions may further comprise one or more stabilizers, including heat stabilizers, viscosity stabilizers, hydrolysis stabilizers, antioxidants, and ultraviolet absorbers. In embodiments, the compositions prepared therefrom may comprise 0% to 40% by weight, such as 0% to 30% by weight, 0% to 20% by weight, 0% to 10% by weight, 0% to 5% by weight, 0% to 1% by weight, 1% to 40% by weight, 1% to 30% by weight, 1% to 20% by weight, or 1% to 10% by weight of stabilizers.
[0025] It should be understood that the composition may further comprise one or more additives as known to those skilled in the art, such as, for example, plasticizers, antistatic agents, dyes, pigments or other colorants, flame retardants, lubricants, reinforcing agents such as glass fibers and sheets, synthetic (e.g., aramid) fibers or pulp, foaming agents or blowing agents, processing aids, slip additives, anti-blocking agents such as silica or talc, release agents, tackifying resins, or combinations of two or more of these. In embodiments, the composition may comprise 0% to 40% by weight, such as 0% to 30% by weight, 0% to 20% by weight, 0% to 10% by weight, 0% to 5% by weight, 0% to 1% by weight, 0% to 0.1% by weight, 1% to 40% by weight, 1% to 30% by weight, 1% to 20% by weight, or 1% to 10% by weight of additives.
[0026] In embodiments, the composition may further comprise additional polymers. Additional polymers may include, but are not limited to, polyolefins, polyolefin elastomers, vinyl copolymers, and ionomers. The composition may comprise 0% to 40% by weight, such as 0% to 30% by weight, 0% to 20% by weight, 0% to 10% by weight, 0% to 5% by weight, 0% to 1% by weight, 0% to 0.1% by weight, 1% to 40% by weight, 1% to 30% by weight, 1% to 20% by weight, or 1% to 10% by weight of additional polymers.
[0027] The molar ratio of epoxy functional groups (generally provided by epoxy-functionalized polyolefins and, where present, by epoxy oils or epoxy resins) to olefinically unsubstituted dicarboxylic acids or their derivatives (generally provided by functionalized polyolefins) can be from 20 to 235, such as 20 to 150, 20 to 40, 40 to 60, 60 to 80, 80 to 100, 100 to 120, 120 to 140, 140 to 160, 160 to 180, 180 to 200, 200 to 220, 220 to 240, 240 to 260, 260 to 280, 280 to 300, 300 to 325, or any combination of two or more of these ranges. As previously stated, without being theoretically limited, it is believed that an excess of acid functional groups in the composition can lead to a decrease in the thermal aging properties of the resulting composition by catalyzing the decomposition of the polyamide compound. Therefore, it is believed that when the molar ratio of epoxy functional groups to unsubstituted olefinic dicarboxylic acids or their derivatives is too low, such as less than 20, the composition will undergo excessive thermal aging. Furthermore, it is believed that when the ratio of epoxy functional groups to unsubstituted olefinic dicarboxylic acids or their derivatives is too high, such as greater than 235, the composition will not be sufficiently toughened for use.
[0028] In some specific embodiments, the molar ratio of the alkyl glycidyl acrylate functional group to the olefinically unsubstituted dicarboxylic acid or its derivative is 16 to 150, such as 25 to 135, 16 to 20, 20 to 30, 30 to 50, 50 to 75, 75 to 100, 100 to 125, 125 to 150, or any combination of two or more of these ranges.
[0029] In some embodiments, the composition may comprise at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, at least 99 wt%, or even at least 99.9 wt% of polyamide; epoxy-functionalized polyolefin; functionalized polyolefin; optionally, inorganic filler; optionally, stabilizer; optionally, additive; and optionally, additional polymers, by weight. In some embodiments, the composition comprises at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, or even at least 99 wt% of the total weight of polyamide, epoxy-functionalized polyolefin, and functionalized polyolefin.
[0030] In some embodiments, the article may comprise a composition. The article may be a molded article, such as an injection-molded article. The article (such as an injection-molded article) may have an impact strength retention rate of equal to or greater than 80%, such as equal to or greater than 85%, equal to or greater than 90%, equal to or greater than 95%, equal to or greater than 98%, or even equal to or greater than 99%, after 1000 hours of heat aging. The article (such as an injection-molded article) may have an impact strength retention rate of equal to or greater than 80%, such as equal to or greater than 85%, equal to or greater than 90%, equal to or greater than 95%, equal to or greater than 98%, or even equal to or greater than 99%, after 1500 hours of heat aging.
[0031] The product may have an initial (before heat aging) impact strength equal to or higher than 650 J / m, such as equal to or higher than 650 J / m, equal to or higher than 675 J / m, equal to or higher than 700 J / m, equal to or higher than 720 J / m, or equal to or higher than 750 J / m.
[0032] The product may have an initial (pre-heat aging) flexural modulus equal to or greater than 1790 MPa, such as equal to or greater than 1825 MPa, equal to or greater than 1875 MPa, or equal to or greater than 1900 MPa.
[0033] The product may have an initial (pre-heat aging) fracture stress equal to or higher than 48 MPa, such as equal to or higher than 49 MPa, equal to or higher than 51 MPa, or equal to or higher than 53 MPa.
[0034] Test Methods
[0035] Density
[0036] Samples for density measurement were prepared according to ASTM D 1928. The polymer sample was pressed for three minutes at 190°C and 30,000 psi, followed by one minute at 21°C and 207 MPa. Measurements were performed within one hour of sample pressing using ASTM D792, Method B.
[0037] Melt Index (I2)
[0038] Melt index or I2 (g / 10 min or dg / min) is measured according to ASTM D 1238, conditions 190°C / 2.16 kg, procedure B.
[0039] Izod Impact
[0040] Impact strength is determined according to ASTM D256.
[0041] Tensile Properties
[0042] Tensile properties (e.g., elongation at break and tensile stress at break) are measured according to ASTM D-638.
[0043] Flexural Properties
[0044] Bending properties (e.g., bending modulus) are measured according to ASTM D-790.
[0045] GMA Level
[0046] GMA levels were measured by nuclear magnetic resonance (NMR) 1 Quantification was performed using 1H NMR. The NMR sample was prepared as follows: Approximately 0.1 g of the sample was added to 3.25 g (by weight) of 50 / 50 1,1,2,2-tetrachloroethane-d2 / perchloroethylene (TCE / PCE) containing 0.001 M Cr(AcAc)3 and approximately 50 ppm butylated hydroxytoluene (BHT) in a Norell 1001-7 10 mm NMR tube. The tube was capped and then heated and vortexed at 115 °C to dissolve and ensure homogeneity. 1H NMR was performed at the sample temperature of 120 °C on a Bruker AVANCE 400 MHz spectrometer equipped with a Bruker high-temperature CryoProbe. Spectra were acquired using ZG pulses, 1.6 s AQ, 16 scans with a 14 s relaxation delay.
[0047] Glycidyl methacrylate (GMA) was quantified using the integrated area of the three epoxy ring protons at approximately 3.2 ppm, 2.8 ppm, and 2.6 ppm. GMA was further quantified using nBA CH2 at concentrations from approximately 3.7 ppm to 4.6 ppm. - O - The n-butyl acrylate (nBA) comonomer was quantified by subtracting twice the molar number of GMA from the integrated area of the protons. Ethylene was quantified using an area of 0.5 ppm to 2 ppm after subtracting the contributions of nBA and GMA to that area.
[0048] MAH Level
[0049] The MAH level is determined using the method described in WO2017116843A1. Where possible, it is preferable to measure the MAH level during manufacturing, as those skilled in the art know that MAH groups can hydrolyze during aging in a natural environment upon exposure to moisture. MAH can be regenerated by heat conditioning in a controlled inert environment at temperatures >150°C.
[0050] Examples
[0051] The following examples illustrate the features of this disclosure, but are not intended to limit the scope of this disclosure. The following experiments analyze the performance of embodiments of the ethylene-based polymers described herein.
[0052] Materials
[0053] MAH-functionalized polyolefin-1 is a maleic anhydride-modified polyethylene elastomer with a density of 0.870 g / cc and a melt index (I2) of 1.6 g / 10 min. The weight percentage of MAH in the copolymer is 0.5%.
[0054] ZYTEL™ 103 is a polyamide 66 (PA66) resin that is commercially available from Celanese.
[0055] Epoxy terpolymer-1 is an E / nBA / GMA terpolymer with a density of 0.94 g / cm³ and a melt index (I²) of 12 dg / min. The composition of epoxy terpolymer-1 is described in more detail in Table 1.
[0056] Table 1: Epoxy Terpolymer Compositions
[0057]
[0058] Sample Preparation
[0059] A series of samples were prepared by compounding the formulations described in Table 2 in a ZSK 26mm twin-screw extruder (TSE) at 270°C to 300°C and a screw speed of 300 rpm. Dumbbell-shaped strips for tensile, cantilever beam impact, and flexural modulus testing were prepared using a Toyo Si-90 injection molding machine. Molding temperatures ranged from 275°C to 290°C, injection pressures were 2000 bar, and cooling times were 20 s. As shown in the table below, the aged samples were aged in an oven at 150°C for 500 hours, 1000 hours, or 1500 hours. The GMA / MAH molar ratios described in Table 2 were calculated according to Equation (I).
[0060]
[0061] Table 2: Sample Compositions
[0062]
[0063] Sample Characterization
[0064] As described in the Test Methods section, each sample was subsequently subjected to tensile, cantilever beam impact, and flexural modulus tests. The results are given in Tables 3-5. Performance retention was calculated according to Equation (II).
[0065]
[0066] Table 3: Notched Charpy Impact Strength
[0067]
[0068] As can be seen from Table 3, after 1000 hours and 1500 hours, EX-A and EX-B showed significantly better impact strength retention than the comparative examples. The exceptions were CE-2 and CE-4, which showed very low initial impact strength. Therefore, while CE-2 and CE-4 retained a significant amount of strength, they did not possess sufficient initial strength for their respective applications.
[0069] Table 4: Stress at Break
[0070]
[0071] As can be seen from Table 4, EX-A, EX-B, and the comparative samples showed acceptable fracture stress retention rates after aging. However, the comparative samples CE-1 and CE-4 showed insufficient initial (0-hour) fracture stress.
[0072] Table 5: Flexural Modulus
[0073]
[0074] As can be seen from Table 5, compared with the comparison samples, EX-A and EX-B both showed excellent flexural modulus greater than 1790 MPa before and after aging.
Claims
1. A composition comprising: Polyamide; Epoxy-functionalized polyolefins, wherein the epoxy-functionalized polyolefins comprise one or more epoxy cyclic functional groups; and Functionalized polyolefins, wherein the functionalized polyolefins comprise polyolefins having an unsubstituted dicarboxylic acid or a derivative thereof with an olefinic bond, and The molar ratio of the epoxy functional group to the unsubstituted olefinic dicarboxylic acid or its derivative is 20 to 235.
2. The composition according to claim 1, wherein the composition further comprises one or more epoxy oils or epoxy resins.
3. The composition according to claim 1 or 2, wherein the epoxy-functionalized polyolefin is a terpolymer comprising α-olefin, alkyl acrylate and glycidyl methacrylate.
4. The composition according to any one of claims 1 to 3, wherein the functionalized polyolefin is grafted with an olefinically unsubstituted dicarboxylic acid or a derivative thereof.
5. The composition according to any one of claims 1 to 4, wherein the functionalized polyolefin comprises having a content of 0.855 g / cm³. 3 Up to 0.890 g / cm 3 Polyethylene elastomer with a certain density.
6. The composition according to any one of claims 1 to 5, wherein the functionalized polyolefin is grafted with 0.1% to 3.0% by weight of maleic anhydride.
7. The composition according to any one of claims 1 to 6, wherein the melt index (I2) of the functionalized polyolefin is from 0.1 g / 10 min to 15 g / 10 min.
8. The composition according to any one of claims 1 to 7, wherein the epoxy-functionalized polyolefin comprises: 1% to 15% by weight of alkyl glycidyl acrylate; and 10% to 40% by weight of alkyl acrylate.
9. The composition according to any one of claims 1 to 8, wherein the epoxy-functionalized polyolefin has a melt index (I2) of 1.0 g / 10 min to 30 g / 10 min as measured according to ASTM D1238 (190 °C / 2.16 kg).
10. The composition according to any one of claims 1 to 9, wherein the molar ratio of the alkyl glycidyl acrylate functional group to the olefinically unsubstituted dicarboxylic acid or its derivative is 20 to 235.
11. The composition according to any one of claims 1 to 10, wherein the composition comprises 60% to 99% by weight of the polyamide; 0.8% to 39% by weight of the epoxy-functionalized polyolefin; and 0.1% to 8% by weight of the functionalized polyolefin.
12. An article comprising the composition according to any one of claims 1 to 11.
13. The article of claim 12, wherein the article is an injection-molded article.
14. The article according to any one of claims 12 to 13, wherein the injection-molded article has an impact strength retention rate of equal to or greater than 80% after 1000 hours of heat aging.
15. The article according to any one of claims 12 to 14, wherein the injection-molded article has an impact strength equal to or greater than 650 J / m, a flexural modulus equal to or greater than 1790 MPa, and a fracture stress equal to or greater than 48 MPa prior to heat aging.
Citation Information
Patent Citations
Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins
US3645992A
Ethylene polymer blend and polymerization process for preparation thereof
US3914342A
Hydrocarbon interpolymer compositions
US4076698A
Interpolymers of ethylene and unsaturated carboxylic acids
US4599392A
Elastic substantially linear olefin polymers
US5272236A
